WAYS TO INCREASE THE COMPETENCE OF LOCAL AUTHORITIES TO ENSURE THE STABILITY OF LOCAL BUDGET REVENUES - Meyliev Obid Rakhmatullaevich; Gofurova. K. (Scholars Digest Publishing, 2023)
The article discusses the powers of local authorities and the basis for their increase in achieving stability in local budget revenues. The possibilities of ensuring the stability of local budget revenues based on the appointment, definition and implementation of the competencies of local authorities are substantiated.
Keywords: local budget, budget balance of local budgets, local budget revenues, local authorities, powers of local authorities, taxes, tax revenues.